Chapter Premessa - Poli, Daniela (Territori, 2020)
The short introduction reconstructs the external history of the texts collected in this volume, which are a reworking of the authors' contributions to the seminar "From territorial heritage to eco-territorial services: towards an operational definition". It also draws a quick sketch of the relationships that urge us to rethink the ecosystem services as eco-territorial services, between territorialist approach, bioregional planning, territorial heritage, and answers to be offered urgently to the problems - climatic, environmental, economic and social - posed by a society in transition.